“I WANT A CAT” KAJIAN STRUKTURAL-SEMIOTIK-PSIKOANALITIK CERPEN “CAT IN THE RAIN” KARYA HEMINGWAY - Siswo Harsono (KAJIAN SASTRA, 2011)
This writing discusses a short story, “Cat in the Rain”, written by Ernest Hemingway by using structural, semiotic, and psychoanalytic approaches. The aims of this writing are to analyze the prime signifier which covers the basic narrative structure, the sequence, plot, and the characters, and the binary oppositions of sender/receiver, subject/object, and helper/opponent, to analyze denotation/connotation/myth, and metonymy/metaphor, and to analyze the hidden meanings of the short story. By using actantial model in dealing with the axis of desire, the subject is the wife and the object is the cat. In the axis of knowledge, the sender is Padrone, and the receiver is the wife. In the axis of power, the helpers are the maid, umbrella, and the mirror; and the opponents are the husband, the rain, and the book. Thus, the protagonist of the story is the wife; and the antagonist is the husband. Semiotically speaking, the short story has three levels of signification, denotation, connotation, and myth. The denotative meaning of “cat” is /pet/, its connotative meaning is //beloved man//, and its mythological meaning is ///phallus///. The denotative meaning of “rain” is /water/, its connotative meaning is //sperm//, and its mythological meaning is ///fertility///. Metonymically speaking, the short story refers to the wife who wants a cat; and metaphorically speaking, it refers to the wife who wants to have a beloved man. The intertextuality of the short story and its illustration includes addition, substitution, deletion, and transposition. In this case, the cat is the animalization of the wife. The latent meaning of the short story relates to the psychosexual problems of its characters.   Keywords: structural-semiotic-psychoanalytic approaches, binary oppositions, metonymy, metaphor, intertextuality, psychoanalysis http://ejournal.undip.ac.id/index.php/kajiansastra/editor/submission/2919